2017
DOI: 10.1016/j.pss.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Spectra and physical properties of Taurid meteoroids

Abstract: Taurids are an extensive stream of particles produced by comet 2P/Encke, which can be observed mainly in October and November as a series of meteor showers rich in bright fireballs. Several near-Earth asteroids have also been linked with the meteoroid complex, and recently the orbits of two carbonaceous meteorites were proposed to be related to the stream, raising interesting questions about the origin of the complex and the composition of 2P/Encke. Our aim is to investigate the nature and diversity of Taurid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…Similar heterogeneity of Taurid physical properties was observed recently by Matlovič et al (2017). Brown et al (2013) suggested that Taurids might drop meteorites.…”
Section: Physical Propertiessupporting
confidence: 83%
“…Similar heterogeneity of Taurid physical properties was observed recently by Matlovič et al (2017). Brown et al (2013) suggested that Taurids might drop meteorites.…”
Section: Physical Propertiessupporting
confidence: 83%
“…Some degree of heterogeneity in Fe/Mg and Na/Mg ratios (typically up to 30% in ternary Na/Mg/Fe content) among meteoroids from one parent object appears to be natural. This is suggested from the wider spectral studies of Leonids, Geminids (Borovička et al 2005), Taurids (Matlovič et al 2017), and Perseids (this work). Sodium enhancement was confirmed in one 49 Andromedid.…”
Section: Halley-typementioning
confidence: 60%
“…12 are dominated by Perseids and Taurids, respectively. All of the Taurid meteoroids analyzed here were observed during the 2015 outburst and were analyzed previously by Matlovič et al (2017).…”
Section: Shower Meteorsmentioning
confidence: 99%
“…As noted in Section 4, JEO meteoroids are of significantly weaker material strength compared to Taurids (Fig. 8), (Spurný et al 2017;Matlovič et al 2017). Furthermore, the estimated size of 2019 MO was only around four meters.…”
Section: Search For the Parent Objectmentioning
confidence: 59%